3464 Readability, Understandability, and Actionability of Inpatient Discharge Instructions: A Health Literacy Perspective - Glick, Alexander (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: Parents often make errors in comprehending and executing their child’s inpatient discharge instructions, putting their child at risk for adverse post-discharge outcomes. Suboptimal provider-caregiver communication has been linked to errors in comprehension and execution of provider instructions, especially for parents with limited health literacy. Few studies have systematically examined features of pediatric inpatient written discharge instructions that may contribute to errors. Our objective was to assess the readability, understandability, and actionability of pediatric inpatient written discharge instructions. METHODS/STUDY POPULATION: This was a cross-sectional analysis of the written discharge instructions (standardized template, content not standardized) provided to parents at an urban public hospital, enrolled as part of a prospective cohort study (n=171) focused on parent ability to comprehend their child’s discharge instructions. Inclusion criteria were: English/Spanish-speaking parents of children ≤12 years old discharged on ≥1 daily medicine. Discharge instructions were assessed for: 1) Readability (Average of 5 formulas [Flesh Reading Ease, Flesch-Kincaid, Gunning Fog, Simple Measure of Gobbledygook, Forcast]), 2) Understandability and actionability (AHRQ Patient Education Materials Assessment Tool [2 independent reviewers; κ>0.8 for both]). RESULTS/ANTICIPATED RESULTS: Mean (SD) reading grade level was 11.4 (0.7); none of the instructions were written at a recommended reading level of 6(th) to 8(th) grade or below. Mean (SD) understandability was 37.7 (6.9)%; mean actionability was 41.7 (8.4)%. All 171 sets of instructions used medical terminology without adequate plain language explanations and included information that was not relevant to the child’s diagnosis and associated care (e.g., obesity counseling, smoking cessation given to a child with appendicitis). None of the sets of instructions presented information in a logical sequence (e.g., diet instructions in more than one location) or included any pictographic information or other visual aids to support the text (e.g., diagram of medication dose within a dosing tool). DISCUSSION/SIGNIFICANCE OF IMPACT: Written discharge instructions provided in the pediatric inpatient setting were suboptimal. Use of a systematic approach to improve discharge instructions, using a health literacy perspective, has the potential to improve post-discharge outcomes in children.